CSVS, a crowdsourcing database of the Spanish population genetic variability. - Peña-Chilet, Maria; Roldán, Gema; Perez-Florido, Javier; Ortuno, Francisco M; Carmona, Rosario; Aquino, Virginia; López-López, Daniel; Loucera, Carlos; Fernandez-Rueda, Jose L; Gallego, Asunción; Garcia-Garcia, Francisco; González-Neira, Anna; et al. (Nucleic Acids Res, 2021)
The knowledge of the genetic variability of the local population is of utmost importance in personalized medicine and has been revealed as a critical factor for the discovery of new disease variants. Here, we present the Collaborative Spanish Variability Server (CSVS), which currently contains more than 2000 genomes and exomes of unrelated Spanish individuals. This database has been generated in a collaborative crowdsourcing effort collecting sequencing data produced by local genomic projects and for other purposes. Sequences have been grouped by ICD10 upper categories. A web interface allows querying the database removing one or more ICD10 categories. In this way, aggregated counts of allele frequencies of the pseudo-control Spanish population can be obtained for diseases belonging to the category removed. Interestingly, in addition to pseudo-control studies, some population studies can be made, as, for example, prevalence of pharmacogenomic variants, etc. In addition, this genomic data has been used to define the first Spanish Genome Reference Panel (SGRP1.0) for imputation. This is the first local repository of variability entirely produced by a crowdsourcing effort and constitutes an example for future initiatives to characterize local variability worldwide. CSVS is also part of the GA4GH Beacon network. CSVS can be accessed at: http://csvs.babelomics.org/.
Keywords: Alleles; Chromosome Mapping; Crowdsourcing; Databases, Genetic; Exome; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genomics; Humans; Internet; Precision Medicine; Software; Spain

VISMapper: ultra-fast exhaustive cartography of viral insertion sites for gene therapy. - Juanes, José M; Gallego, Asunción; Tárraga, Joaquín; Chaves, Felipe J; Marin-Garcia, Pablo; Medina, Ignacio; Arnau, Vicente; Dopazo, Joaquin (BMC Bioinformatics, 2017)
BACKGROUND: The possibility of integrating viral vectors to become a persistent part of the host genome makes them a crucial element of clinical gene therapy. However, viral integration has associated risks, such as the unintentional activation of oncogenes that can result in cancer. Therefore, the analysis of integration sites of retroviral vectors is a crucial step in developing safer vectors for therapeutic use. RESULTS: Here we present VISMapper, a vector integration site analysis web server, to analyze next-generation sequencing data for retroviral vector integration sites. VISMapper can be found at: http://vismapper.babelomics.org . CONCLUSIONS: Because it uses novel mapping algorithms VISMapper is remarkably faster than previous available programs. It also provides a useful graphical interface to analyze the integration sites found in the genomic context.
Keywords: Base Sequence; Genetic Therapy; Genetic Vectors; High-Throughput Nucleotide Sequencing; Humans; Internet; User-Computer Interface; Virus Integration